Tuning the CuxO nanorod composition for efficient visible light induced photocatalysis12. Issue 7 (24th November 2015) - Basnet, Pradip; Zhao, Yiping
Abstract : Single and mixed phase Cu2 O/CuO nanorod arrays prepared by thermal oxidation were tested for photocatalysis and photoelectrochemical properties. Abstract : A facile, low cost, and convenient method to fabricate Cu x O ( x = 1, 2) nanorod (NR) arrays is demonstrated by thermally oxidizing Cu NRs fabricated by oblique angle deposition. The single phase Cu2 O and CuO, and mixed phase Cu2 O/CuO polycrystalline NRs can be tuned simply by varying the thermal oxidation temperature. These Cu x O NRs exhibit excellent visible light photocatalytic activity for both cationic (methylene blue) and anionic (methyl orange) dye degradations. When used as a photocathode, they also show good photoelectrochemical performance, especially the mixed phase Cu2 O/CuO NRs. The maximum stable photocurrent density is observed to be 0.24 mA cm −2 under a simulated solar light. Incident photon-to-current efficiencies are found to be 20% and 44% at incident light wavelengths λ = 500 nm and 400 nm, respectively. These results show that the Cu x O NRs fabricated through the oxidation method can be a suitable candidate for efficient visible light active photocatalysts for energy applications as well as for wastewater treatment.